Rocotos bloom - Rey de Werra, Miguel A. (1984)
When any parishioner arrives in Ollachea, province of Carabaya, department of Puno, they immediately collide with poverty and misery. For about 25 years, the Prelature of Ayaviri has insisted on sending priests and pastoral agents to this remote area and nothing or almost nothing has changed, despite the invasion of the territory with supplies from Caritas or silver from Europe. Why?